The vestigial gene product provides a molecular context for the interpretation of signals during the development of the wing in Drosophila. - Klein, T.; Martinez Arias, A. (Development, 1999)
The vestigial (vg) gene of Drosophila plays a central role in the development and patterning of the wing: loss of vestigial results in failures in wing development and ectopic expression of vestigial leads to the development of ectopic wings. The wing-specific regulation of vestigial is mediated through two enhancers: (1) the Boundary Enhancer (vgBE) is early acting and becomes restricted to the wing margin, and (2) the Quadrant Enhancer (vgQE), acts later and is responsible for the expression of vestigial in the developing wing blade. These enhancers receive regulatory inputs from three signalling pathways: wingless, decapentaplegic and Notch/Suppressor of Hairless. Our experiments show that the vestigial gene product is also an input in the regulation of vestigial expression. In particular, Vestigial provides an important input for the regulation of the activity of the vgQE acting in concert with Wingless and Decapentaplegic. Our results suggest how interactions between vgBE and the vgQE mediated by Vestigial can explain the interactions between the wing margin and the wing blade during the growth of the wing. We further show that Vestigial and Notch collaborate with Wingless to subdivide and pattern the wing blade. These results lead us to propose a general role for Wingless during development in which it stabilizes cell fate decisions that have been implemented by other molecules.